Pralines des Voyageurs: An Iconic Intercultural Food - Bouchard, Valérie; Charbonneau, Patrick; de Valicourt, Justine (Cuizine)

(untitled) (McGill University Library, 2024)
Pralines are well-known French and New Orleans delicacies synonymous with both high-calorie count and refinement. In the 18th and early 19th centuries, the confection also had a rougher edge. After substituting almonds and refined sugar by indigenous ingredients—corn and maple sugar—it became an iconic travel food for explorers and traders of the North American continent. This article traces the spread of pralines from their metropolitan origin to their frontier use, as the semantic range of the term gradually shifted. We also attempt to reconstruct a contemporary equivalent to the historical recipe.